175m-100m+48,750=50,500-175m

Simple and best practice solution for 175m-100m+48,750=50,500-175m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 175m-100m+48,750=50,500-175m equation:



175m-100m+48.750=50.500-175m
We move all terms to the left:
175m-100m+48.750-(50.500-175m)=0
We add all the numbers together, and all the variables
175m-100m-(-175m+50.5)+48.750=0
We add all the numbers together, and all the variables
75m-(-175m+50.5)+48.75=0
We get rid of parentheses
75m+175m-50.5+48.75=0
We add all the numbers together, and all the variables
250m-1.75=0
We move all terms containing m to the left, all other terms to the right
250m=1.75
m=1.75/250
m=1/142.85714285714

See similar equations:

| 4x-2=3x+$ | | (7b+21)/(5b-18)=0 | | (9x+5)x=0 | | 0.125x=0,025(5x+1) | | 16-2m/3=5 | | 1/7.5=6x/2 | | x-2x=3-3 | | 15x+463=52x+54 | | 47831+23478x=578+5179x | | 5x-1=60 | | 0.4(y+10)+0,6y=2 | | 0x+1=10x+31 | | 6xx7.5=0 | | (2x+7)(9x+6)=0 | | 7x-2=4+3x | | X+{3(x+1)}-8=43 | | X+{3(x+1)-8=43 | | (2x+6)(9x+7)=0 | | 41x+22=41x+87 | | X+3(x+1)-8=43 | | (4x+2)(5x+8)=0 | | x/3-1=3x/2 | | x/3+5=x-1/2 | | 10(s-)=-99 | | 90x+90=1+70x | | 6(h+7)=13 | | -5-4+7c=12 | | -1.1-0.7x=0.8x+5.5 | | 100(10)^2p=0 | | x/6-10=-5 | | X+3(x+1)=59 | | 3x+5/6=4x-7/6 |

Equations solver categories